THE ALGORITHM FOR CORRECTING A MODE OF THE POWER SUPPLY SYSTEM THAT TAKES THE TRANSFORMATIONS AND HETEROGENEITY OF THE NETWORK INTO ACCOUNT - O. I. Alexandrov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
The problem of expeditious correction has great practical value for operation of the power supply system and is one of the most important and complex challenges of an automated control system of an electrical power system. Its complexity is due to the dynamics and nonlinearity of equations of state of an electrical network, recorded as related to node voltages, and also due to multiply connected network elements. Attempts to solve the problem by using the theory of sensitivity lead to the appearance – in addition to the matrices of the generalized parameters of the network – of several sensitivity matrices, for the formation of which sufficiently effective algorithms for fast recalculation of the matrices when switching schemes are not yet developed. It results in a need to calculate matrix data anew at each switching, or to recognizing some mode as a basic one considering other modes virtually unchanged at relatively small deviations of the parameters, which, in its turn, leads to additional errors. The new method of calculation of the power flows distribution in the network is proposed that based is not on physical modeling of the structure of the investigated circuit, but on the mathematical modeling of the structure of the equations describing the flow distribution, thereby removing the limitations imposed by heterogeneity and the presence of transformations.